Uniform admissions, unequal access: Did the top 10% plan increase access to selective flagship institutions?. (April 2022) - Klasik, Daniel; Cortes, Kalena E.
Abstract: The Top 10% Plan admissions policy has now been in place in Texas for over two decades. We analyze 18 years of post-Top 10% Plan data to look for evidence of increased access to the selective Texas flagship campuses among all Texas high schools. We describe new sending patterns from high schools that did not have a history of sending students to the flagship campuses. Our analysis reveals an increase in the likelihood that high schools in non-suburban areas sent students to the flagship campuses, but ultimately little to no equity-producing changes over this 18-year period in terms of regular attendance at flagships by students who attended high schools without a previous sending history. Thus, the purported high school representation benefits of the policy may not go as far as advocates might have hoped in terms of generating equity of access to the flagship campuses in the state.